Antibiotic-resistant nutants identified from nodules of uninoculated soybeans grown in a strongly acidic soil - Ayanaba, A.; Wong, A.L. (1982)
Two hypotheses that antibiotic-resistant nodule isolates from uninoculated soybeans grown in a strongly acidic soil were naturally occurring rhizobia which had acquired resistance to spectinomycin and streptomycin or were contaminants from adjacent, inoculated treatments, were tested in laboratory experiments. Soybean nodule isolates (166) as well as 48 cowpea and 89 Rhizobium japonicum strains were used in tests of resistance to six concentrations (0–500 μg ml−1) of kanamycin, spectinomycin and streptomycin, tolerance of stresses of pH 4.6, with or without 50 μm Al, and serological cross-reactivity.